Radiation Segmentectomy or Ablative External Beam Radiation Therapy as Initial Treatment for Solitary Hepatocellular Carcinoma: A Multicenter Experience - De la Garza-Ramos C; Montazeri SA; LeGout JD; Lewis AR; Frey GT; Paz-Fumagalli R; Hallemeier CL; Rutenberg MS; Ashman JB; Toskich BB (Journal of Hepatocellular Carcinoma)
Cynthia De la Garza-Ramos,1 S Ali Montazeri,1 Jordan D LeGout,2 Andrew R Lewis,1 Gregory T Frey,1 Ricardo Paz-Fumagalli,1 Christopher L Hallemeier,3 Michael S Rutenberg,4 Jonathan B Ashman,5 Beau B Toskich1 1Division of Interventional Radiology, Mayo Clinic Florida, Jacksonville, FL, USA; 2Department of Radiology, Mayo Clinic Florida, Jacksonville, FL, USA; 3Department of Radiation Oncology, Mayo Clinic Rochester, Rochester, MN, USA; 4Department of Radiation Oncology, Mayo Clinic Florida, Jacksonville, FL, USA; 5Department of Radiation Oncology, Mayo Clinic Arizona, Phoenix, AZ, USACorrespondence: Beau B Toskich, Division of Interventional Radiology, Mayo Clinic Florida, Jacksonville, FL, USA, Tel +1 (904) 953-1496, Email toskich.beau@mayo.eduPurpose: Radiation segmentectomy (RS) and ablative external beam radiation therapy (EBRT) are now accepted, definitive, local therapies for hepatocellular carcinoma (HCC). This report aimed to describe the clinical outcomes of RS and EBRT for treatment-naïve, solitary, HCC.Methods: A multicenter retrospective review was performed of all patients treated with RS or EBRT from March 2016 through September 2023. Inclusion criteria were initial treatment for solitary HCC ≤ 8 cm and absence of macrovascular invasion or extrahepatic disease. Outcomes were censored for liver transplantation (LT).Results: Eighty-six patients (RS: 58; EBRT: 28) met inclusion criteria. The EBRT cohort had older patients (median 76 vs 66 years, p < 0.001), larger tumors (median 3.7 vs 2.4 cm, p < 0.001), and worse performance status (p = 0.02). The RS cohort had more patients with ≥ grade 3 liver fibrosis (p < 0.001). Radiologic complete response (rCR) was achieved in 97% of RS and 82% of EBRT patients (p = 0.02). Median time to rCR was 1 month (95% CI: 0.9– 1.1) after RS and 7 months (95% CI: 6– 7) after EBRT (p < 0.001). The 1-year local control was 97% vs 93% for RS and EBRT, respectively (p = 0.80). Subsequent LT was performed in 48% of RS and 11% of EBRT patients with tumor complete pathologic response rates of 76% (n=22/28) and 33% (n=1/3), respectively. Progression free survival at 1-year was 87% after RS vs 80% after EBRT (p = 0.26). 1- and 2-year overall survival was 88% and 85% after RS vs 84% and 59% after EBRT (p = 0.34).Conclusion: RS and EBRT are effective therapies for solitary HCC. Treatment should be determined via multidisciplinary discussion based on individual patient characteristics.Keywords: hepatocellular carcinoma, radiation segmentectomy, stereotactic body radiation therapy, proton beam therapy, ablation